Initial Dosage Optimization of Tacrolimus in Pediatric Patients With Thalassemia Major Undergoing Hematopoietic Stem Cell Transplantation Based on Population Pharmacokinetics. Issue 4 (April 2021) - Zhou, Siru; Zhang, Ren; Lv, Chunle; Lu, Jiejiu; Wei, Yinyi; Li, Chengxin; Chen, Ming; Li, Qiaochuan; Liu, Taotao
Background: Hematopoietic stem cell transplantation (HSCT) is an effective treatment for hematological disorders. Tacrolimus is widely used after HSCT, but it has highly interindividual variable pharmacokinetics. Population pharmacokinetics (PPK) researches of tacrolimus in children with β-thalassemia major (β-TM) undergoing HSCT are insufficient. Objective: To establish a PPK model of tacrolimus in children with β-TM and optimize initial dosing regimen for achieving target concentration of 5 to 15 ng/mL. Methods: Data on patients aged <18 years were retrospectively collected from January 2017 to December 2018. PPK analysis and Monte Carlo simulations were performed using nonlinear mixed-effects modeling. Results: A data set of 55 patients with 332 concentrations was included. A 2-compartment model could best describe the pharmacokinetics of tacrolimus. The body surface area and gender were significant covariates in the final model. The typical value of clearance, the distribution volume of the central room, the distribution volume of the peripheral room, and the intercompartmental clearance were 5.05L/h, 4.33L, 155L, and 6.22L/h, respectively. The optimal initial dosing regimen of 0.03, 0.04, 0.05, 0.06, and 0.10 mg/kg were appropriate for female children with a weight (WT) of 50 to 10 kg. The regimen of 0.04, 0.05, 0.06, 0.07, and 0.12 mg/kg is suitable for male children with a WT of 50 to 10 kg. The probability of target attainment (PTA) of each regimen reached 91%. Conclusion and Relevance: A stable PPK model of tacrolimus was established. The proposed dosage regimen reached a good PTA, which could provide a reference for tacrolimus therapy.